Life retrospective of Russian emigrants in China - Krasnoyarova, Anna Alexandrovna; Popkova, Tatyana Dmitrievna; Kondakov, Boris Vadimovich (Opción, 2019)
The article attempts to reproduce an integral picture of the world of Russian emigrants and the functioning of two Russian cultural enclaves that arose in China in the 1920s and 1930s based on the examples of a comparative analysis of two novels published at the beginning of the XXI century. As a result, the variety of views, styles, and forms born by the authors creates a kind of atmosphere in which readers are indulged, feeling a sense of ownership of the ongoing actions. In conclusion, the Russian culture of Shanghai and Harbin can rightfully be considered interethnic and cross-cultural.